(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
The article deals with the effective use of goats and female goats in the production of goats and female goats in the herd of woolly goats, dealing with each male and female goat individually, selecting and sorting according to their parental ancestors, as well as selection traits useful for the farm, feeding, productive woolly goats, woolly female goats issues such as escape with and taking measures to escape the barren goats in time will be covered.